Intelligent Object-Oriented Approach to Dynamic Energy Systems’ Modelling - Verlan, A.; Sterten, Jo (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2020)
Proposed object-oriented approach and general architecture of intellectual software for mathematical modelling of dynamic energy systems. Introduced and considered in detail an architecture of knowledge bases for modelling of systems described by linear integral equations. Considered a knowledge-based system as a composition of a specific functional network and an expert system.